Consequence on Optical Properties of ZnS Thin-Film Deposited by RF Magnetron Sputtering with Varying Substrate Temperatures - Gupta A.K.S.; Ahamed E.M.K.I.; Quamruzzaman M.; Matin M.A.; Rahaman K.S.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Buffer layers; Energy gap; Film preparation; II-VI semiconductors; Infrared devices; Lime; Magnetron sputtering; Near infrared spectroscopy; Optical properties; Optoelectronic devices; Semiconducting zinc compounds; Semiconductor devices; Substrates; Sulfur compounds; Thin film solar cells; Wide band gap semiconductors; Zinc sulfide; Alternative buffer layers; Morphological properties; Multi-layer thin film; Radio frequency magnetron sputtering; rf-Magnetron sputtering; Soda lime glass substrate; Substrate temperature; UV-vis-NIR spectroscopy; Thin films